Associations of anger, vital exhaustion, anti-depressant use, and poor social ties with incident atrial fibrillation: The Atherosclerosis Risk in Communities Study. (13th January 2020) - Garg, Parveen K; Claxton, J'Neka S; Soliman, Elsayed Z; Chen, Lin Y; Lewis, Tené T; Mosley, Thomas; Alonso, Alvaro
Abstract: Background: We examined the relationships of anger, vital exhaustion, anti-depressant use, and poor social ties with incident atrial fibrillation in a biracial cohort of middle and older-aged adults. Methods: This analysis included 11, 445 Atherosclerosis Risk in Communities Study participants who were free of atrial fibrillation at baseline in 1990–1992. Vital exhaustion was assessed at baseline and defined as a score in the highest quartile on the 21-item Vital Exhaustion Questionnaire. Baseline anti-depressant use was self-reported. The Spielberger Trait Anger Scale to assess anger and both the Interpersonal Support Evaluation List and the Lubben Social Network Scale to assess social ties were also administered at baseline. The primary outcome was incident atrial fibrillation throughout 2016, identified by electrocardiogram, hospital discharge coding of atrial fibrillation, and death certificates. Results: A total of 2220 incident atrial fibrillation cases were detected over a median follow-up of 23.4 years. After adjusting for age, race-center, sex, education, and height, participants in the 4th Vital Exhaustion Questionnaire quartile (referent = 1st Vital Exhaustion Questionnaire quartile) and those reporting anti-depressant use were at increased risk for atrial fibrillation (hazard ratio = 1.45, 95% confidence interval 1.29–1.64 for Vital Exhaustion Questionnaire; hazard ratio = 1.37, 95% confidence interval 1.11–1.69 for anti-depressant use). The increased atrial fibrillation risk observed for 4th Vital Exhaustion Questionnaire quartile participants remained significant after additional adjustment for relevant comorbidities (hazard ratio = 1.20; confidence interval 1.06–1.35). No significant associations were observed for anger or poor social ties with development of atrial fibrillation. Conclusions: Vital exhaustion is associated with an increased risk of incident atrial fibrillation.